Pengadopsian Wilayah Bebas dari Korupsi dan Wilayah Birokrasi Bersih dan Melayani oleh Kelurahan Bumi Ayu - Dita Fisdian Adni; Satrio Abdillah; Yulia Herawati (Universitas Teuku Umar, 2023)
Wilayah Bebas Dari Korupsi (WBK) and Wilayah Birokrasi Bersih Dan Melayani (WBBM) is a predicate given to units/work units in Local Government with as low as echelon III that perform service functions. The term WBK or WBBM is not wrong if it is adopted by government units / work units in echelon IV, namely Urban Village because Urban Village is a work unit that also provides services to the community. In the adoption of WBK and WBBK independently in Bumi Ayu Urban Village, Dumai subdistrict, Dumai city, there are several problems. The first is that almost all employees and office holders in Bumi Ayu Urban Village do not understand the meaning of WBK or WBBM. The next problem is the service mechanism that does not meet the standards of WBK and WBBM. The method used in this community service is to provide counseling and assistance to the Bumi Ayu Urban Village government apparatus. It can be concluded that counseling and assistance on the adoption of WBK and WBBM in Bumi Ayu Urban Village in an effort to improve services to the community runs successfully and smoothly and Bumi Ayu Urban Village officials increasingly understand the importance of the predicate of WBK and WBBM.